Cardiovascular Risk Factors and Differential Transcriptomic Profile of the Subcutaneous and Visceral Adipose Tissue and Their Resident Stem Cells - Gemma Arderiu; Carmen Lambert; Carlos Ballesta; Fabrizio Moscatiello; Gemma Vilahur; Lina Badimon (Cells, 2020)
Background: The increase in the incidence of obesity and obesity-related cardiovascular risk factors (CVRFs) over the last decades has brought attention on adipose tissue (AT) pathobiology. The expansion of AT is associated with the development of new vasculature needed to perfuse the tissue; however, not all fat depots have the same ability to induce angiogenesis that requires recruitment of their own endothelial cells. In this study we have investigated the effect of different CVRFs, on the angiogenic capacity of the subcutaneous (SAT) and visceral (VAT) adipose tissue and on the function of their mesenchymal cell reservoir. Methods: A transcriptomic approach was used to compare the different angiogenic and inflammatory profiles of the subcutaneous and visceral fat depots from individuals with obesity, as well as their resident stem cells (ASCs). Influence of other risk factors on fat composition was also measured. Finally, the microvesicles (MVs) released by ASCs were isolated and their regenerative potential analyzed by molecular and cellular methodologies. Results: Obesity decreases the angiogenic capacity of AT. There are differences between SAT and VAT; from the 21 angiogenic-related genes analyzed, only three were decreased in SAT compared with those decreased in VAT. ASCs isolated from both fat depots showed significant differences; there was a significant up-regulation of the VEGF-pathway on visceral derived ASCs. ASCs release MVs that stimulate endothelial cell migration and angiogenic capacity. Conclusions: In patients with obesity, SAT expresses a greater number of angiogenic molecules than VAT, independent of the presence of other CVRFs.